Age-Related Serum Biochemical Reference Intervals Established for Unweaned Calves and Piglets in the Post-weaning Period - Yu, Kuai; Canalias, Francesca; Solà-Oriol, David; Arroyo, Laura; Pato, Raquel; Saco, Yolanda; Terré, Marta; Bassols, Anna (Frontiers in Veterinary Science, 2019)
The purpose of the present study is to establish the influence of age on serum biochemistry reference intervals (RIs) for unweaned calves and recently-weaned piglets using large number of animals sampled at different ages from populations under different season trials. Specifically, MR-fed calves trials from April - July 2017 (n=60); from December 2016 - March 2017 (n=76) and from April - August 2018 (n=57) and one group of healthy weaned piglets (n=72) were subjected to the study. Serum enzymes and metabolites of calves at age of 24h (24h after colostrum intake), 2, 5 and 7 weeks from merged trials and piglets at 0, 7 and 14 days post-weaning (at 21, 28 and 35 days of age) are studied. The major effect that causes difference is from different ages whereas no major trial- or sex-biased differences were noticed. In calves, ALT, AST, GGT, GPx, SOD, NEFAs, triglycerides, glucose, creatinine, total protein and urea were greatly elevated (p<0.001) at 24h compared with other ages; glucose, creatinine, total protein and urea constantly decreased along the age; cholesterol’s lowest level (p<0.001) was found in 24h compared with other ages and the levels of haptoglobin remained unchanged (p>0.1) during the study. In comparison with the adult RIs, creatinine from 24h, NEFAs from 2w, GGT from 5w and urea from 7w are fully comparable with RIs or lie within RIs determined for adult. In piglets, no changes were noticed on glucose (p>0.1) and haptoglobin (p>0.1) and there were no major changes on hepatic enzymes (ALT, AST and GGT), total protein, creatinine and urea even though several statistical differences were noticed on 7 days of post-weaning. Cholesterol, triglycerides, NEFAs, cortisol and PigMAP were found increased (p<0.05) while TNF-alpha was found least concentrated (p<0.001) at 0 days post-weaning compared with other times. Moreover, the RIs of creatinine and GGT are fully comparable with RIs or lie within RIs determined for adult. In conclusion, clinical biochemistry analytes RIs were established for unweaned calves and recently-weaned piglets and among them some can vary at different ages.